HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP DENGAN PEMAKAIAN ALAT PELINDUNG DIRI (APD) PEKERJA DI PABRIK PTPN7 KABUPATEN SELUMA - Kuntari Qisti, Ardiyani (Poltekkes Kemenkes Bengkulu, 2021)
The problem that is found in the PTPN7 factory in Seluma district is that workers do not use Personal Protective Equipment (PPE), PPE has been provided by the factory but not used by workers. workers who do not use PPE because they lack and interfere with work activities. Most workers do not use the Personal Protective Equipment (PPE) in full at the PTPN7 factory in Seluma district. The purpose of the study was to determine the relationship between the level of knowledge and attitudes with the use of PPE workers at the PTPN7 factory in Seluma Regency. The research method used was a survey method with a cross sectional study design. The total sample was 153 workers, univariate and bivariate analysis with chi-square test.The results of the study were some respondents (32.7%) had less knowledge,more than half of the respondents (60.8%) had an unfavorable attitude, and most respondents (59%) were not complete in using PPE. There is a relationship between knowledge with the use of personal protective equipment (PPE) ρ value = 0.00 (ρ value ≤ 0.05), attitude with the use of personal protective equipment (PPE) ρ value = 0.022 (ρ value ≤ 0.05). This study provides information to PTPN7 seluma district factories to understand the importance of using PPE for security and safety, especially when workingThe problem that is found in the PTPN7 factory in Seluma district is that workers do not use Personal Protective Equipment (PPE), PPE has been provided by the factory but not used by workers. workers who do not use PPE because they lack and interfere with work activities. Most workers do not use the Personal Protective Equipment (PPE) in full at the PTPN7 factory in Seluma district. The purpose of the study was to determine the relationship between the level of knowledge and attitudes with the use of PPE workers at the PTPN7 factory in Seluma Regency. The research method used was a survey method with a cross sectional study design. The total sample was 153 workers, univariate and bivariate analysis with chi-square test.The results of the study were some respondents (32.7%) had less knowledge,more than half of the respondents (60.8%) had an unfavorable attitude, and most respondents (59%) were not complete in using PPE. There is a relationship between knowledge with the use of personal protective equipment (PPE) ρ value = 0.00 (ρ value ≤ 0.05), attitude with the use of personal protective equipment (PPE) ρ value = 0.022 (ρ value ≤ 0.05). This study provides information to PTPN7 seluma district factories to understand the importance of using PPE for security and safety, especially when working